Alterations in Cardiac Function Following Endurance Exercise Are Not Duration Dependent - Coates, Alexandra M.; King, Trevor J.; Currie, Katharine D.; Tremblay, Joshua C.; Petrick, Heather L.; Slysz, Joshua T.; Pignanelli, Christopher; Berard, Jordan A.; Millar, Philip J.; Burr, Jamie F. (Frontiers in Physiology, 2020)
Cardiac function has been shown to transiently decrease following prolonged exercise, with greater durations related to increased impairment. However, the prospective assessment of exercise duration on cardiac performance is rare, and the influence of relative exercise intensity is typically not assessed in relation to these changes. The aim of this study was to determine whether progressively longer running distances over the same course would elicit greater cardiac impairment. The present investigation examined cardiac alterations in 49 athletes, following trail-running races of 25km, 50km, 80km, and 160km, performed on the same course on the same day. Echocardiography, including conventional and speckle tracking imaging, was performed with legs-raised to 60° to mitigate alterations in preload both pre-and-post race. Race-intensities were monitored via heart rate (HR). Following the races, mean arterial pressure (Δ-11±7mmHg, P<0.0001), and HR (Δ19±14bpm, P<0.0001) were altered independent of race distance. Both left and right ventricular (LV and RV) diastolic function were reduced (ΔLV E/A -0.54±0.49, P<0.0001; ΔRV A’ +0.02±0.04m/s, P=0.01) and RV systolic function decreased (ΔTAPSE -0.25±0.9cm, P=0.01), independent of race distance. Cardiac impairment was not apparent using speckle tracking analysis with cubic spline interpolation. While race duration was unrelated to cardiac alterations, increased racing HR was related to greater RV base dilation (r =-0.37, P=0.03). Increased time spent at higher exercise intensities was related to reduced LV ejection fraction following 25km (r=-0.81, P=0.03), LV systolic strain rate following 50km (r=0.59, P=0.04), and TAPSE (r=-0.81, P=0.03) following 80km races. Increased running duration did not affect the extent of exercise-induced cardiac fatigue, however, intensity may be a greater driver of cardiac alterations.